2014
DOI: 10.1099/jmmcr.0.002634
|View full text |Cite
|
Sign up to set email alerts
|

Primary peritonitis caused by Raoultella ornithinolytica in a 53‐year‐old man

Abstract: Introduction: Raoultella ornithinolytica is a Gram-negative bacillus. This bacillus was until recently often confused with Klebsiella spp. It is known primarily for causing histamine fish poisoning or scombroid syndrome, and rarely causes human infections. This case report discusses a patient who presented with generalized primary peritonitis due to R. ornithinolytica.Case presentation: A 53-year-old Scandinavian man resident in Botswana, sub-Saharan Africa, presented to the emergency department shortly after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…This series of human infections caused by R. ornithinolytica managed at four university hospital centres in France over the last 12 years is the largest reported to date. A literature search identified 86 reported cases of R. ornithinolytica (formerly Klebsiella ornithinolytica), [3][4][5][6][7][8][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and half of these cases were reported in 2015. 10,12,[24][25][26] A high rate of hospital-acquired infection was observed in the present study (49%), which may be explained by the high proportion of patients who had undergone invasive procedures (48%) involving, for example, urinary catheters, mechanical ventilation, and port catheters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This series of human infections caused by R. ornithinolytica managed at four university hospital centres in France over the last 12 years is the largest reported to date. A literature search identified 86 reported cases of R. ornithinolytica (formerly Klebsiella ornithinolytica), [3][4][5][6][7][8][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and half of these cases were reported in 2015. 10,12,[24][25][26] A high rate of hospital-acquired infection was observed in the present study (49%), which may be explained by the high proportion of patients who had undergone invasive procedures (48%) involving, for example, urinary catheters, mechanical ventilation, and port catheters.…”
Section: Discussionmentioning
confidence: 99%
“…21 Among the 86 isolates reported in the literature, 80% were resistant to amoxicillin, 17% to amoxicillin-clavulanic acid, 10% to third-generation cephalosporins, 12% to quinolones, 13% to co-trimoxazole, 15% to piperacillin-tazobactam, 7% to aminosides, and 7% to carbapenems. [3][4][5][6][7][8][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Few of these studies reported cases of R. ornithinolytica infection with isolates resistant to multiple antibiotics, including KPC 14 and NDM-1 strains. 27 In this study, the proportions of isolates resistant to ceftriaxone, quinolones, and aminosides were a little bit lower than reported in the literature (4%, 6%, and 1%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…R. ornithinolytica is known as one of the bacteria in charge for scombroid poisoning, a toxic condition due to the ingestion of fish with high levels of histamine (Masashi et al, 2002); however, in the last decade it was considered as an emerging pathogen in humans (Seng et al, 2016) involved in urinary tract infection (García-Lozano et al, 2013;Nakasone et al, 2015), septicemia (Kaya et al, 2014;Sueifan et al, 2016), bacteremia (Mau & Ross, 2010;Hadano et al, 2012;Haruki et al, 2014;Sekowska et al, 2015), peritonitis (Sibanda, 2014), enteric fever (Morais et al, 2009), biliary infection (Cleveland et al, 2014;de Jong et al, 2014), infected "diabetic foot" (Solak et al, 2011;Kabbara & Zgheib, 2015) and artritis (Venus et al,2016). However, cases of infection were always related to some factor of primary malignancy or immune deficiency (Chun et al, 2015;Boattini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%